Determination of the efficiency of hafnium carbide and tantalum carbide coatings deposited on exchange membrane fuel cells (2021)
The energy efficiency of the hafnium carbide and tantalum carbide membranes (electrolyte) deposited through the PVD technique was determined from the systems simulation under operating conditions of parallel plates connected in series. Bipolar plates are used for two purposes: to conduct electrical current between the cells, and the other is to distribute hydrogen and oxygen. Thus, bipolar plates are used for two functions: one is to conduct electrical current between the cells, and the other is to distribute hydrogen and oxygen. We have developed two bipolar plate patterns, which include serpentine patterns and the bio-inspired flow field pattern. The coatings (serpentine) characterization was carried out using surface characterization techniques such as atomic force microscopy and structural identification by X-ray diffraction, allowing the analysis of the coating structure to determine the efficiency of carbide-based cathodes for hydrogen production from electrochemical impedance spectroscopy.